2000
DOI: 10.1046/j.1525-1373.2000.22501.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid System and Cytokine Network

Abstract: Many advances have been made in the last few years concerning our understanding of the receptors and ligands composing the cannabinoid system. Likewise, the science surrounding cytokine biology has advanced enabling us to measure these proteins more precisely as well as understand and interpret the meaning of changes in their levels. Scientists wishing to study the health consequences of smoking marijuana as well as understand the possible role of endogenous cannabimimetic ligands in immune regulation have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(117 citation statements)
references
References 45 publications
3
109
1
4
Order By: Relevance
“…As noted earlier, the effects of cannabinoids on IL-6 have not been well studied, but there are several reports that do not suggest they down-regulate this cytokine [4,11]. The other two studies cited earlier included either a baseline comparison or a comparison with a control group of non-cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, the effects of cannabinoids on IL-6 have not been well studied, but there are several reports that do not suggest they down-regulate this cytokine [4,11]. The other two studies cited earlier included either a baseline comparison or a comparison with a control group of non-cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…This clinical trial examined the orexigenic effects of megestrol acetate, the cannabinoid dronabinol, versus the combination of both for the treatment of cancer-associated anorexia and weight loss (work submitted) and found that megestrol acetate was superior to dronabinol in its orexigenic effects in the doses prescribed. It should be noted that a few previous studies have examined the effect of cannabinoids on IL-6 and that overall these studies suggest these agents do not down-regulate this cytokine [4,11]. The goals of the translational component reported here included the following: (1) to determine whether megestrol acetate was associated with a decline in serum IL-6 concentrations compared to dronabinol or combination therapy; and (2) to determine whether changes in serum IL-6 after 1 month of orexigenic therapy were associated with changes in appetite, weight, and quality of life.…”
Section: Introductionmentioning
confidence: 92%
“…AEA modulates the production and function of a variety of cytokines in mast and basophilic cells through the cannabinoid receptors (24). RBL-2H3 cells are of immune origin and express FAAH (25) and the CB 2 receptor (26).…”
Section: Arachidonoyl Ethanolamide (Aea)mentioning
confidence: 99%
“…Mo du la ti on ver schie de ner Zy to ki ne: IFN-γ, IL-12 und IL-2 é; IL-1 Á (è) [46] 1062 | Der Nervenarzt 9 · 2005…”
Section: Die En Do Ge Nen Can Na Bi Noidre Zep To Renunclassified
“…Sig ni fi kan te Im mun sup pres si on, ins be son de re der zel lu lä ren Im mu ni tät (An zahl und Funk ti on von B-und T-Lym pho zy ten so wie Ma kro pha gen); Ver mitt lung ver mut lich über CB2-Re zep to ren [32,55,89] Hem mung der An ti tu mor-und an ti vi ra len Wir kung von Ma kro pha gen [11,12,100] Hem mung der An ti gen prä sen ta ti on durch Ma kro pha gen [61] Hem mung der Mig ra ti on von Ma kro pha gen via CB1-und CB2-Re zep to ren [81] Hem mung der TH1-Zel len [46] Mo du la ti on ver schie de ner Zy to ki ne: IFN-γ, IL-12 und IL-2 é; IL-1 Á (è) [46] des Ze re bel lums (Ko or di na ti on von Be wegung, Ba lan ce, Hal tung), des Hip po kampus (u. a. wich tig für Ge dächt nispro zesse) und der Ba sal gan gli en (Kon trol le der Be we gung; . Ta bel le 2).…”
Section: Mo Du La Ti On Des Im Mun Sys Tems Via Cb2-re Zep Tor Im Mununclassified